2017
DOI: 10.2174/1568026617666170130123520
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Currently Available Antimalarials

Abstract: Despite the seemingly large number of the drugs currently available for malaria treatment, this arsenal is limited due to the narrow variation of their mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Additionally, in the same year, ∼212 million cases of malaria were noted worldwide, particularly in African regions. Advanced prevention and treatment techniques and malaria eradication initiatives, including insecticide‐treated bed nets, insecticide sprays, and artemisinin‐based combination therapies (ACTs), have collectively decreased the lethality of malaria (∼4% per year), with a 40% decrease in the number of clinical malaria cases between 2000 and 2015 . However, certain factors, including increased resistance of the parasite to drugs, extended period of infection in the human host, high cost of drugs and lack of new potent drugs, are still obstacles to controlling the disease .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in the same year, ∼212 million cases of malaria were noted worldwide, particularly in African regions. Advanced prevention and treatment techniques and malaria eradication initiatives, including insecticide‐treated bed nets, insecticide sprays, and artemisinin‐based combination therapies (ACTs), have collectively decreased the lethality of malaria (∼4% per year), with a 40% decrease in the number of clinical malaria cases between 2000 and 2015 . However, certain factors, including increased resistance of the parasite to drugs, extended period of infection in the human host, high cost of drugs and lack of new potent drugs, are still obstacles to controlling the disease .…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, the global market has been waiting for new drug molecules with novel modes of action. In the early 2000s, a new efficient drug, arterolane, was presented as an effective treatment in the form of a fixed‐dose combination with piperaquine and was marketed in India and several African countries . However, this combination therapy still requires approval from the World Health Organization (WHO) for general usage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to World Health Organization (WHO), about 216 million cases and 445,000 deaths from malaria were reported in 2016 ( WHO, 2018c ). Furthermore, the resistance to antimalarial drugs is a common and growing issue and constitutes a substantial threat for populations in endemic regions ( Gorobets et al, 2017 ; Menard and Dondorp, 2017 ). In a study reported by Zhang et al (2013) , a data set of 3,133 compounds reported as active or inactive against P. falciparum chloroquine susceptible strain (3D7) was used to develop QSAR models.…”
Section: Practical Applications Of Qsar-based Virtual Screeningmentioning
confidence: 99%